The importance of ball throw-in in football - Basic, D.; Tomasko, J. (Sport Science - International Scientific Journal of Kinesiology, 2017)
Based on 88 matches of 2014/2015 Croatian first football league we determined the importance of ball throw-in in regard to final outcome of the match and the competition. Using Mann-Whitney test and Pearson coefficient, we collected data proving that throw-in as a situational efficacy indicator does not pose a significant difference to the winning team (p=0,42), nor does it influence the final placement in league system of competition (r=0,38). The results point to the need for a more quality restart and finding alternative ways to develop this part of the match.